Development and validation of a scale to measure team communication behaviors - Hartner-Tiefenthaler, Martina; Loerinc, Ivana; Hodzic, Sabina; Kubicek, Bettina (Frontiers in Psychology, 2022)
With the COVID-19 pandemic, remote work was increased all over the globe. As a consequence, workers had to adapt their communication behaviors to smoothly coordinate work in their flexible teams (i.e., when team members divide work between the office and their homes). In order to capture the most relevant team communication behaviors, we constructed and validated the team communication scale (TCS) drawing on relational coordination theory. Our scale comprises three dimensions: focused communication, knowledge sharing and spontaneous communication. We validated the scale with 130 teams from diverse organizations. Confirmatory factor analyses supported the proposed three-factor structure. Moreover, all three dimensions showed convergent validity with team planning and discriminant validity with time-spatial flexibility. Also, predictive validity with collective efficacy and team viability was achieved for focused communication and knowledge sharing. Spontaneous communication only predicted collective efficacy, but not team viability. We conclude that the TCS is a reliable and valid measure for assessing team communication behaviors.